Investigation of locoregional metastatic behavior in low-grade malignant tumors of the parotid gland - Kapsalas, Andreas; Thimsen, Vivian; Varga, Regina; Agaimy, Abbas; Sievert, Matti; Balk, Matthias; Rupp, Robin; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of low-grade malignant tumors of the parotid gland following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for low-grade malignant tumors of the parotid gland by complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 94 patients formed our study sample (50 females, 44 males, female to male ratio: 1.14). The mean age was 59 years (range 15–95 years). The mean number of lymph nodes in the specimen from complete parotidectomy was 3.33 (range: 0–12). The mean number of involved lymph nodes in the parotid gland was 0.05 (range: 0–1). The mean number of lymph nodes in the specimen from the ipsilateral neck dissection was 16.2 (range 4–42). The mean number of involved lymph nodes in the neck dissection specimen was 0.09 (range: 0–2). Comparison of T1-T2 vs. T3-T4 cases revealed no statistically significant difference concerning the tumorous involvement of the lymphatic network (x2 = 0.719, p = 0.396). Conclusion: Low-grade primary malignant tumors of the parotid gland are characterized by an initially low metastatic potential, which justifies conservative forms of surgical treatment.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy